GEOPOLITIC IMPERATIVES FOR GLOBAL DEVELOPMENT ASYMMETRIES - Kravchuk, Nataliia (Journal of European Economy, 2017)
The paper is concentrated on functional determinants of category – conceptual apparatus within the tandem of «geo-political imperatives – asymmetry of global development» The author generalized theoretical and conceptual principles of ideological paradigms of geo-politics, and offered retrospective conceptual classification of fundamental political and philosophical basics of geopolitics (according to academic schools). The matrix of geo-political imperatives of global development asymmetries is constructed. Also the geo-political pragmatism is revealed, and theoretical and methodological constructions are argued for modern innovative civilization geo-politics. Following from the extrapolation of in ternational methodological concept of Stanley Hoffmann the paper analyses asymmetries of global development in horizontal, vertical, functional, and ideo logical dimensions.